Genetic Variants in the Protein S (PROS1) Gene and Protein S Deficiency in a Danish Population - Larsen, Ole Halfdan; Kjaergaard, Alisa D.; Hvas, Anne-Mette; Nissen, Peter H. (TH Open, 2021)
Protein S (PS) deficiency is a risk factor for venous thromboembolism (VTE) and can be caused by variants of the gene encoding PS (PROS1). This study aimed to evaluate the clinical value of molecular analysis of the PROS1 gene in PS-deficient participants. We performed Sanger sequencing of the coding region of the PROS1 gene and multiplex ligation-dependent probe amplification to exclude large structural rearrangements. Free PS was measured by a particle-enhanced immunoassay, while PS activity was assessed by a clotting method.A total of 87 PS-deficient participants and family members were included. In 22 index participants, we identified 13 PROS1 coding variants. Five variants were novel. In 21 index participants, no coding sequence variants or structural rearrangements were identified. The free PS level was lower in index participants carrying a PROS1 variant compared with index participants with no variant (0.51 [0.32–0.61] vs. 0.62 [0.57–0.73] × 103 IU/L; p < 0.05). The p.(Thr78Met) variant was associated with only slightly decreased free PS levels (0.59 [0.53–0.66] × 103 IU/L) compared with the p.(Glu390Lys) variant (0.27 [0.24–0.37] × 103 IU/L, p < 0.01). The frequency of VTE in participants with a coding PROS1 variant was 43 and 17% in the group with normal PROS1 gene (p = 0.05).In conclusion, we report 13 PROS1 coding variants including five novel variants. PS levels differ by PROS1 variant and the frequency of VTE was higher when a coding PROS1 variant was present. Hence, molecular analysis of the PROS1 gene may add clinical value in the diagnostic work-up of PS deficiency.
Keywords: protein S deficiency; PROS1; venous thromboembolism; inherited thrombophilia